Experimental study of in-plane flexural behavior of screen-grid insulated concrete form rectangular and T-shaped walls. (15th November 2021) - Lopez, Alvaro; Bazaez, Ramiro; Leiva, Gilberto; Loyola, René; Gómez, Miguel
Highlights: In-plane cyclic behavior of SGICF walls is experimentally and analytically investigated. Rectangular-and T-shaped SGICF walls were tested in this study which have not been addressed in previous studies. Behavior of SGICF walls is quite comparable with conventional RC shear walls. Results indicate ductile and stable response as well as high dissipating energy capacity for all walls. Edge elements shown to be ineffective for increasing the displacement capacity of ICF walls. Flexural resistance models for solid cross-section RC members are applicable for ICF walls. Abstract: Screen Grid Insulated Concrete Form (SGICF) walls are gaining popularity in the construction of low and mid-rise buildings due to their unique constructability and insulation properties. In order to validate and ensure the safety of this novel construction system in the face of seismic loads, experimental testing aimed to provide information regarding its nonlinear behavior is of significant relevance. This paper aims to describe analytically and experimentally the in-plane flexural behavior of SGICF panels. An analytical model is presented to estimate the design parameters considering the material properties and the element geometry. Ten test specimens were constructed and tested under monotonic and cyclic in-plane lateral loading to assess the model's effectiveness. Test units were divided into two groups, each constructed using different prefabricated forms made of expanded polystyrene. The first group comprised six rectangular-shaped section walls whereas group two comprised four T-shaped section walls. All specimens were designed and detailed to obtain a flexure-controlled response, considering the presented analytical model. Results showed a ductile and stable response for all test specimens, with yielding of the longitudinal reinforcement and compression crushing of the extreme concrete fibers. This study shows that SGICF walls can reach large inelastic deformations, as well as a stable response, similar to that of conventional reinforced concrete (RC) walls with similar geometric properties. Furthermore, it was verified that flexural resistance models for solid cross-section RC members are applicable to Insulated Concrete Form (ICF) walls, taking into account section discontinuities.